Intestinal Parasitic Infections in Homosexual Men at a San Francisco Health Fair - Markell, Edward K. (1983)
In a sample of homosexual men attending a San Francisco Bay Area health fair, there were strikingly higher prevalence rates of intestinal parasitic infections compared with rates in a control group of health plan members who had a routine multiphasic health examination. Physicians treating homosexual men must be aware of the likelihood of such infections, whether or not the patients are symptomatic.